A MORPHOSYNTACTIC ANALYSIS OF MALALA’S MESSAGE IN HER UNO SPEECH (Contemporary Journal of Social Science Review, 2025)
This paper examines the speech of Malala Yousafzai to the United Nations by analyzing the key features of her speech in the use of effective linguistic devices, particularly syntactic and morphological features that render her speech very persuasive. The study relies on discourse analysis and linguistic theories to identify the interrelated roles of sentence structures, morphemes, and rhetoric decisions to formulate the universal movement of Malala in the direction of girls' education and peace. Declarative and imperative sentence structures, along with parallelism and anaphora, enhanced authority and emotional appeal. Morphological characteristics and inflectional morphemes make her message even clearer and ideologically more effective. The results suggest that the patterns of language and discourse used by Malala are generally consistent with the established activist literacy anticipations, but with specific parameters, which demonstrate her unique cultural and individual identity. The current paper is a response to the lack of linguistic research that considers syntax and morphology as persuasion tools to activate activist messages, since most of the previous literature on the Malala Yousafzai speeches has been dedicated to the critical study of discourse and the rhetorical tools employed in the speeches. The analysis of the 2013 speech of Malala Yousafzai at the United Nations is conducted with the help of a qualitative morphosyntactic analysis revealing the major syntactic constructions (declarative and imperative types of sentences, allelism, parallelism, and anaphora) and morphological patterns (derivational and inflectional morphemes) used in the speech. The results indicate that these grammatical decisions play a major role in the building of authority, emotional persuasion, and ideological explicitness, especially in the themes of resistance, empowerment, and education advocacy. This study addresses a research gap by examining how morphosyntactic patterns are strategically employed in youth activism discourse as a means of persuasion and how these patterns contribute to culture-specific persuasion. The positive reception of Malala's speech demonstrates the need for further research on its rhetorical skills and the significant role of language in contestation and international interactions, which enhance credibility among individuals.